Direct Genetics Referral Pathway for High-Grade Serous Ovarian Cancer Patients: The "Opt-Out" Process. (2nd April 2019) - McGee, Jacob; Peart, Teresa M.; Foley, Norine; Bertrand, Monique; Prefontaine, Michel; Sugimoto, Akira; Ettler, Helen; Welch, Stephen; Panabaker, Karen
Abstract : Purpose . In order to meet a clinical need for better pathways to access genetic testing for ovarian cancer patients, we implemented and reviewed an opt-out referral process for genetic consultation whereby a referral is automatically sent to genetics following a pathological diagnosis of HGSC. Methods . Following implementation of the opt-out referral process, each month a list of new cases of HGSC was generated from the synoptic pathology report and forwarded directly to the Cancer Genetics clinic. Using an advanced directive, patients were automatically referred for genetic counselling two months after surgery. If the patient declined genetic counselling (opted-out) after discussion with their surgeon within the two months after surgery, the Genetic Counsellor was informed and the patient was removed from the referral process. Results . Between January 1, 2015, and December 31, 2017, 168 women were diagnosed with HGSC, of whom 167 received a referral for genetic consultation. In only one case the referral was cancelled by the surgeon, resulting in a referral rate of 99.4%. By the end of the study period, 133 women attended a genetics consultation appointment and 125 (94%) agreed to proceed with genetic testing. Among those who completed genetic testing, 15% tested positive for a BRCA1 or BRCA2 gene mutation. Of the women who tested positive for a BRCA1/2 mutation, 56% had no family history of breast or ovarian cancer. Conclusions . The opt-out referral process described in this study is s a feasible, effective, and patient-centred approach to increase access to BRCA1/2 testing for patients with ovarian cancer.